Cover Feature: Deactivation and Regeneration of Sulfonated Carbon Catalysts in Hydrothermal Reaction Environments (ChemSusChem 13/2018). Issue 13 (2nd July 2018) - Scholz, David; Kröcher, Oliver; Vogel, Frédéric
Abstract : The Cover Feature illustrates the important role of Brønsted acid catalysts in the sustainable production of fuels and chemicals from biomass. Because of their higher stability, sulfonated carbon catalysts are demonstrated to be the Brønsted acid catalyst of choice for applications in aqueous phase reaction environments. Their deactivation can be fully overcome by firstly exploiting the structure–stability dependence of sulfonic acid groups in carbonaceous materials, and secondly by suppressing ion‐exchange‐induced proton leaching. More information can be found in the Full Paper by Scholz et al. on page 2189 in Issue 13, 2018 (DOI: 10.1002/cssc.201800678 ).